UJI CEMARAN BAKTERI COLIFORM PADA DEPOT AIR MINUM ISI ULANG DI KECAMATAN TERNATE SELATAN - Setiawan, Stefani Titis Evanda; Ismail Rahman,; Dewi Darmayanti, (Journal of Innovation Research and Knowledge, 2025)
According to the World Health Organization (WHO) and the American Public Health Association (APHA), drinking water quality is determined by the presence and number of bacteria, with Coliform bacteria commonly used as microbiological indicators of contamination and potential presence of pathogenic microorganisms such as Escherichia coli. In 2022, the highest incidence of diarrhea in Ternate City was reported in Kalumata Village, South Ternate District, raising concerns regarding the microbiological quality of refill drinking water consumed by the community. This study aimed to determine the presence of Coliform bacteria contamination in refill drinking water depots in South Ternate District. A laboratory-based experimental study was conducted by collecting 18 refill drinking water samples from different depots, which were examined using the Most Probable Number (MPN) method. The results showed that 14 of 18 samples (77.78%) were positive for Coliform bacteria, with MPN values exceeding 0 per 100 mL. In conclusion, Coliform bacteria contamination was found in the majority of refill drinking water depots in South Ternate District, indicating that several depots did not meet the microbiological quality standards for drinking water.